Effects of feed intake level on efficiency of microbial protein synthesis and nitrogen balance in Boran steers consuming tropical poor-quality forage. Issue 2 (4th March 2019) - Wassie, Shimels Eshete; Ali, Asep Indra Munawar; Korir, Daniel; Butterbach-Bahl, Klaus; Goopy, John; Merbold, Lutz; Schlecht, Eva; Dickhoefer, Uta
ABSTRACT: This study aimed at evaluating the effects of feed intake level on the efficiency of rumen microbial protein synthesis (EMPS), nitrogen (N) excretion, and N balance in twelve 18-months old Boran ( Bos indicus ) steers with initial average liveweight of 183 kg (standard deviation (SD) 15.2). The experiment followed a 4 × 4 complete Latin Square design with four dietary treatments tested in four periods. Each period ran for 5 weeks with 3 weeks of adaptation and 2 weeks of sample collection; separated by 2 weeks of re-feeding. Steers were fed at 100%, 80%, 60%, and 40% of their metabolisable energy requirement for maintenance (MER, referred to as MER100, MER80, MER60, and MER40, respectively). Steers receiving MER80, MER60, and MER40 were only fed Rhodes grass hay. MER100 steers were offered Rhodes grass hay at 80% of their MER and cottonseed meal and sugarcane molasses at each 10% of MER. Mean daily dry matter intake differed between treatments ( p < 0.001) and ranged between 2.1 kg/animal (SD 0.13) in MER40 and 4.5 kg/animal (SD 0.31) in MER100. Urinary N excretion and N balance did not differ between MER80, MER60, and MER40. According to contrast test, declining feed intake level from MER80 to MER40 reduced duodenal microbial crude protein flow ( p < 0.001), but did not alter the EMPS (g microbial N/kg digestible organic matter intake). Yet, if scaled to N intake, EMPS increased ( p < 0.049), whereas total N and faecal N excretions decreased linearly with declining intake level ( p < 0.001 for both variables). At similar grass hay intake, duodenal microbial crude protein flow was 41% higher in MER100 than in MER80 steers ( p < 0.001). In cattle offered poor-quality tropical forage below their MER, the very low EMPS and thus microbial protein supply aggravate the negative effects of low dietary nutrient and energy intakes in periods of feed shortage.